A Subject-Centric Credential Management Method based on the Verifiable Credentials - Lim, Seungjoo; Rhie, Min Hyung; Hwang, Dong Yeop; Kim, Ki Hyung (International Conference on Information Networking, 2021)
In this paper, a subject-centric structure is proposed that improves the holder-centric structural problems of verifiable credentials developed for self-sovereign identities. Holder-Centric structured verifiable credentials represent a structure in which a holder can control the credentials even if it is not a subject. This structure allows the holder to attempt authentication or transfer credentials without the subject's permission. The subject may lose some control over the credential, thus losing the meaning of self-sovereign identity. We propose a subject-centric structure that allows the subject to control over the transferred verifiable credentials.
Keywords: Credential management; Structural problems; Authentication Method; Blockchains; Decentralized Identifiers; Self-Sovereign Identity; Verifiable Credentials